Pengaruh Metode Discovery Learning Terhadap Peningkatan Pemahaman Konsep Peserta Didik (Studi Kuasi Eksperimen pada Kompetensi Dasar Elastisitas Permintaan dan Penawaran di Kelas X Akuntansi SMK Negeri 1 Bandung Tahun Ajaran 2013/2014) - Zakiyah Tsauroh Islamiah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2017)
This research is conducted to reveal the influence of Discovery Learning method toward students’ concept understanding improvement on Introduction of Economy and Business subject in SMKN 1 Bandung. The method used in this research is quasi experimental with nonequivalent pretest-posttest control group design. The data analysis teknik with parametric statistical, test of difference (paired samples t-test and independent samples t-test), gain score and effect size calculationused in this research is SPSS v21. The result shown that the use of Discovery Learning method is more effective toimprove the understanding of the concept than the ExpositoryLearning method does.